IMPROVING THE WRITING ABILITY USING MIND MAPPING TECHNIQUE FOR THE FIRST GRADERS OF STIKES MUHAMMADIYAH KENDAL IN THE ACADEMIC YEAR OF 2018/2019 - SRY DEWI (Wiralodra English Journal, 2020)
The research attempts to investigate the result of students’ writing ability through the use of Mind Mapping Technique. It also describes the implementation of mind mapping technique in teaching writing, describes the students’ response and describes the students’ improvement. The subjects were The First Graders of STIKES Muhammadiyah Kendal in the Academic Year of 2018/2019. The type of this research is a classroom action research. In this research there are two cycles, and every cycle consisted of three meetings, and the end of each meeting the researcher conducts the post test to measure the improvement of the students’ writing ability. The data are collected by using observation lists, interview, field notes, documentation, and writing test. In analyzing data the researcher describes the mean of the students based on their score to know the students’ improvement in every cycle. There are two techniques to analyze the data. They are qualitative and quantitative method. To enhance the trustworthiness of the data and to reduce the subjectivity in analyzing the data, the researcher uses triangulation method. The result of this research is mind mapping is an appropriate technique to be used in improving the students’ writing ability.